Gender-specific effects of unemployment on family formation: a cross-national perspective - Christian Schmitt (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
This paper investigates the impact of unemployment on the propensity to start a family. Unemployment is accompanied by bad occupational prospects and impending economic deprivation, placing the well-being of a future family at risk. I analyze unemployment at the intersection of state-dependence and the reduced opportunity costs of parenthood, distinguishing between men and women across a set of welfare states. Using micro-data from the European Community Household Panel (ECHP), I apply event history methods to analyze longitudinal samples of first-birth transitions in France, Finland, Germany, and the UK (1994-2001). The results highlight spurious negative effects of unemployment on family formation among men, which can be attributed to the lack of breadwinner capabilities in the inability to financially support a family. Women, in contrast, show positive effects of unemployment on the propensity to have a first child in all countries except France. These effects prevail even after ontrolling for labour market and income-related factors. The findings are pronounced in Germany and the UK where work-family conflicts are the cause of high opportunity costs of motherhood, and the gender-specific division of labour is still highly traditional. Particularly among women with a moderate and low level of education, unemployment clearly increases the likelihood to have a first child.
Keywords: J13; J24; J64; C41; 330; Family formation; fertility; unemployment; cross-national comparison; Arbeitslosigkeit; Fruchtbarkeit; Geschlecht; Familie; Eltern; Kinder; Vergleich; Familiensoziologie; EU-Staaten